PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM PEMBANGUNAN DESA RANAH BARU KECAMATAN KAMPAR KABUPATEN KAMPAR - Sadila Rahayu; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
study the phenomenon is manifested in the lack of enthusiasm in thecommunity development program undertaken,  ranging from determination of the development programs to the construction implements selected.  This study aims to determine the level of Community Participation in Rural Development Programme Implementation New realm Kampar Kampar district,  and to determine the factorsthat influence the level of community participation in the village of New Realm.Concepts used in this study is according to Cohen and Uphof in Dwiningrumwho say that participation can be distinguished as follows: participation in decision making,  participation in the implementation,  participation in decision-benefits, participation in the evaluation,  and in this study the authors wanted to focus onparticipation in the implementation of development. Descriptive qualitative researchmethods.  To perform data collection,  this study using interviews,  observation,  anddocumentation.From the results it can be seen that the Community's Participation in Rural Development Programme Implementation New Domains Kampar Kampar district is still in the category of "not maximized". Because in this study we can see that the level of community participation in development undertaken is still lacking,  it is because people are not fully able to provide their participation in development, this was due to several factors, namely, age, gender, education, employment and incomeand length of stay. Expected from the results of this study Village Government NewDomains can be increased efforts to invite the community to participate in the NewRealm of the village development program that will come, and is expected also thatthe villagers of New domains can also increase the participation in villagedevelopment programs that will come,  in addition  to the results of this study also found that people often reasoned that the work can not be abandoned, resulting in less public participation, it may be necessary for different mechanisms at the level ofJom FISIP Volume 2 No.1 Februari 2015 2implementation of the subsequent development so that the enthusiasm of the community to participate more stable future.Keywords: Participation, Community, development